ASUHAN KEBIDANAN KOMPREHENSIF PADA NY. “A” DI PRAKTIK MANDIRI BIDAN HJ. HENDRIWATI, S.ST KECAMATAN BANUHAMPU KABUPATEN AGAM - Azura Dewi Anjelita; Yuliza Anggraini; Chyka Febria (Ensiklopedia of Journal, 2026)
Maternal and infant mortality remain major health problems faced by almost all countries, with Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) serving as indicators of a nation's health development success (World Health Organization [WHO], 2024). In Agam Regency, based on the 2024 Health Profile, 11 maternal deaths were recorded from 5,811 live births, or approximately 189.30 per 100,000 live births, mostly caused by hemorrhage (Dinas Kesehatan Kabupaten Agam, 2025). Comprehensive midwifery care, or continuity of care (CoC), is an approach considered effective in reducing MMR and IMR through continuous services from pregnancy, labor, postpartum, newborn care, to family planning (Badan Pusat Statistik [BPS], 2025; Sandall et al., 2021). This article aims to implement comprehensive midwifery care for a pregnant woman through the postpartum and newborn period at the Independent Midwife Practice (PMB) of Hj. Hendriwati, S.ST. The method used was a case study with Varney's seven-step management approach and SOAP documentation applied to a single subject, Mrs. “A”, aged 32 years, G2P1A0H1, from the first contact at 33–34 weeks of gestation (18 February 2026) through the postpartum period (23 April 2026) at PMB Hj. Hendriwati, S.ST, Banuhampu Subdistrict, Agam Regency. The results showed that the third-trimester pregnancy, labor, newborn, and postpartum period of Mrs. “A” proceeded physiologically without complications; the baby was born spontaneously at 19.00 WIB, female, weighing 3,200 grams, 48 cm in length, with an APGAR score of 8/9. All stages of care provided were in accordance with existing standards and theory, so no gap was found between theory and field practice. The study concludes that comprehensive midwifery care using Varney's management and SOAP documentation can be implemented thoroughly and continuously, supporting the safety and well-being of both mother and infant.Keywords: Comprehensive Midwifery Care; Continuity of Care; Labor; Newborn; Postpartum; Third Trimester Pregnancy